Stress solution for functionally graded adhesive joints. (15th October 2016) - Stein, N.; Weißgraeber, P.; Becker, W.
Abstract: The present work provides a new model for the stress analysis of functionally graded adhesive lap joints with composite adherends. It is applicable to various joint configurations such as single lap joints, L-joints, T-joints, reinforcement patches, corner joints or balanced double lap joints. The modelling approach follows the concept of general sandwich-type analyses that consider only the overlap region of the joint with any combination of section forces and moments. To take into account shear deformations of the adherends, First Order Shear Deformation Theory is employed and bending-extension coupling of laminated adherends is covered. Several adhesive joint designs with various adhesive Young's modulus variations are investigated and the obtained adhesive stress distributions are compared to results of detailed finite element analyses. In general, a very good agreement is observed. The present model accurately renders that the adhesive peak stresses can be significantly reduced by the functional grading of the adhesive. Further, the effects of different functional grading functions of the adhesive Young's modulus on the adhesive stresses are studied and discussed. The paper concludes with design considerations for functionally graded adhesive joints.